Code Switching Used by Kimmy Jayanti in "iLook" Program on NET TV: Sociolinguistics Study - Nurul Ihsani Gunawan; Hero Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze and investigate the various forms of Kimmy Jayanti's used code switching in the NET TV program "iLook," utilizing the code switching theory presented by (Dewi, 2021). The goals of this study are to 1) analyze the dominant types of code switching, and 2) to explain what are the functions of code switching used by Kimmy Jayanti her language in the "iLook" program on NET TV. This study used a qualitative method and the data were collected from the script of episode. The result of this study shows that there are three types of code switching used by Kimmy Jayanti in "iLook" program on NET TV: in detail, there are 1 intra-sentential switching, 2 inter-sentential switching, and 2 tag switching. There are 7 reasons of Kimmy Jayanti code switch her language: 1 data of talking about a particular topic, 1 data of quoting somebody else, 1 data of  showing empathy about something, 1 data of interjection, 1 data of repetition used for clarification, 1 data of expressing group identity, and 1 data of clarifying the speech content.